1‐Alkynyltriazenes as Functional Analogues of Ynamides. (16th September 2015) - Perrin, Florian G.; Kiefer, Gregor; Jeanbourquin, Loïc; Racine, Sophie; Perrotta, Daniele; Waser, Jérôme; Scopelliti, Rosario; Severin, Kay
Abstract: The chemical reactivity of 1‐alkynyltriazenes has been investigated and is found to parallel the reactivity of ynamides. The similarity in reactivity of these two classes of compounds is demonstrated by addition reactions with acids, by cycloaddition reactions with ketenes, tetracyanoethene, and cyclopropanes, as well as by intramolecular cyclization reactions. The presence of reactive triazene groups in the products enables subsequent transformations. Overall, our results suggest that 1‐alkynyltriazenes should become valuable reagents in synthetic organic chemistry.